LINC02389/miR-7-5p Regulated Cisplatin Resistance of Non-Small-Cell Lung Cancer via Promoting Oxidative Stress - Peng Ma; Wen Han; Cunying Meng; Xiaohong Tan; Pengfei Liu; Lei Dong (Analytical Cellular Pathology)
Background. Non-small-cell lung cancer (NSCLC) is one of the most common malignancies worldwide, and cisplatin-based chemotherapy is the main treatment for NSCLC. However, cisplatin resistance of NSCLC cells is a major challenge for NSCLC treatment. Materials and Methods. qRT-PCR and Western blot were performed to detect the expression of LINC02389 and miR-7-5p in NSCLC tissues and cell lines. Cell counting kit-8 (CCK-8) assay and flow cytometry assay were applied to exam cell proliferation and apoptosis rate of NSCLC cells. The interaction between LINC02389 and miR-7-5p was verified by dual luciferase reporter gene assay, RNA pull-down assay, and RNA immunoprecipitation (RIP) assay. Additionally, cisplatin-resistant NSCLC cells were generated to assess the biological function of LINC02389 and miR-7-5p in cisplatin resistance of NSCLC. Results. LINC02389 was highly expressed in NSCLC tissues and was correlated with poor prognosis of NSCLC patients. Knockdown of LINC02389 inhibited cell proliferation and promoted cell apoptosis of NSCLC, whereas miR-7-5p knockdown exerted the opposite effects. Moreover, LINC02389 negatively regulated the expression of miR-7-5p. In addition, LINC02389 was overexpressed, yet miR-7-5p was downregulated in cisplatin-resistant NSCLC cells compared with their parental cells. Moreover, oxidative stress biomarkers were overexpressed in cisplatin-resistant cells and were regulated by LINC02389. Besides, LINC02389 could reverse the inhibitory effect of cisplatin on NSCLC cells, which was partially reversed by attenuating the expression of miR-7-5p. Conclusion. Our research firstly demonstrated that lncRNA LINC02389 acted as an oncogene to promote progression, oxidative stress, and cisplatin resistance through sponging miR-7-5p and may provide therapeutic targets for NSCLC.